PENGARUH KEAHLIAN AKUNTANSI DAN KEUANGAN KOMITE AUDIT DAN DEWAN KOMISARIS TERHADAP MANAJEMEN LABA (Studi Empiris Pada Perbankan Yang Terdaftar Di Bursa Efek Indonesia Periode 2019-2020) - R. Triwigati Ningsih; Maslichah Maslichah; Arista Fauzi Kartika Sari (Universitas Islam Malang, 2021)
This study aims to determine the effect of the accounting and financial expertise of the audit committee and the board of commissioners on earnings management. The case study in this study is a banking company listed on the Indonesia Stock Exchange for the 2019-2020 period. Sampling using purposive sampling technique. Data analysis using multiple regression analysis. The samples obtained in this study were 46 companies that met the sample criteria. The results of this study are the results of testing the variables of audit committee accounting expertise, audit committee financial expertise, board of commissioners accounting expertise, board of commissioners financial expertise have a simultaneous effect on earnings management. The test results show that the audit committee with accounting expertise has a positive effect on earnings management. The test results show that the audit committee with financial expertise has a positive effect on earnings management. The test results show that the board of commissioners who have accounting expertise has a positive effect on earnings management. The test results show that the board of commissioners who have financial expertise has a positive effect on earnings management. Keywords: Accounting Expertise, Financial Expertise, Accounting Expertise Board of Commissioners Earnings Management, Audit Committee.